‘Abqariyat al-Lughah al-‘Arabīyah wa-Dawruhā fī al-Taqārub al-Ma‘rifī wa-al-Talāquḥ al-Thaqāfī bayn al-Shu‘ūb - Abdullah Alsuwaiket (Al-Ma’rifah, 2018)
The Arabic language is the spirit of the Arab nation, the title of its identity, and the inclusion of its culture, and when it is preserved by its people, they will be able to be the builders of others’ minds and the proponents of its flags among the languages of nations and peoples. Accordingly, the significance of the study mentioned the geniality of the Arabic language, its properties, its spread in the world. The problem of the study is the universality of the Arabic language after Islam, its major properties, the extent of its spread, its impact. The study will follow the analytical descriptive methodology in tracing this problem and studying its terms. The study revealed the universal position of the Arabic language among other languages of the world that made it a title of human civilization, cultural reference, and the tool of communication between the Arab peoples and non-Arab.